Ornidazole-Induced Recurrent Encephalopathy in a Chinese Man: A Rare Case Report and Literature Review - Tang, Rong; Liang, Jia; Li, Yuanfang; Wu, Tingting; Zhang, Yuhao; Ma, Yu; Liu, Xu (Frontiers in Neurology, 2021)
Ornidazole-induced encephalopathy (OIE) is seldom seen in clinics. In this study, we report a new case of a patient who had taken 1000mg ornidazole daily for nearly 4 years because of suspected diarrhea and proctitis and presented with such subacute symptoms as unsteady gait, slurred speech, and psychiatric disorder. These symptoms were significantly relieved 3 days after the patient stopped taking ornidazole. When he took this medicine again, however, similar symptoms occurred 4 months later, which were again reduced after 4 days of drug discontinuation. After the second onset, abnormal signals were identified around the aqueduct of the midbrain, around the fourth ventricle, and in the dentate nuclei of cerebellum bilaterally. After 9 days of drug discontinuation, lesions disappeared in the magnetic resonance imaging (MRI) results. According to clinical manifestations, imaging features, and the reduced symptoms after drug withdrawal, we clinically diagnosed the patient with OIE. This paper also reviews the literature on OIE. Only 5 cases (including our case) have been reported, all of whom presented with cerebellar ataxia and dysarthria, and 3 with additional mental symptoms such as agitation and irritability. All 5 patients had abnormal lesions in the dentate nucleus of the cerebellum bilaterally, among whom 4 also had lesions in the corpus callosum, and 3 around the periaqueduct of the midbrain. After withdrawal of ornidazole, symptoms in all patients vanished or were alleviated, and 3 of them showed reduced or disappeared lesions in a head-MRI reexamination. Overall, OIE has rarely been reported. Our case report and literature review show that the lesions in the cerebellum, corpus callosum, and brainstem can be reversed. The main manifestations of the lesions— cerebellar ataxia, dysarthria, and mental symptoms — quickly weaken or disappear after drug withdrawal, with good prognosis. Nevertheless, clear pathogenesis has yet to be further investigated.